Accuracy and impact of risk assessment in the primary prevention of cardiovascular disease: a systematic review. Issue 12 (18th April 2006) - Brindle, P; Beswick, A; Fahey, T; Ebrahim, S
Abstract : Objective: To determine the accuracy of assessing cardiovascular disease (CVD) risk in the primary prevention of CVD and its impact on clinical outcomes. Design: Systematic review. Data sources: Published studies retrieved from Medline and other databases. Reference lists of identified articles were inspected for further relevant articles. Selection of studies: Any study that compared the predicted risk of coronary heart disease (CHD) or CVD, with observed 10-year risk based on the widely recommended Framingham methods (review A). Randomised controlled trials examining the effect on clinical outcomes of a healthcare professional assigning a cardiovascular risk score to people predominantly without CVD (review B). Review methods: Data were extracted on the ratio of the predicted to the observed 10-year risk of CVD and CHD (review A), and on cardiovascular or coronary fatal or non-fatal events, risk factor levels, absolute cardiovascular or coronary risk, prescription of risk-reducing drugs and changes in health-related behaviour (review B). Results: 27 studies with data from 71 727 participants on predicted and observed risk for either CHD or CVD were identified. For CHD, the predicted to observed ratios ranged from an underprediction of 0.43 (95% CI 0.27 to 0.67) in a high-risk population to an overprediction of 2.87 (95% CI 1.91 to 4.31) in a lower-risk population. In review B, four randomised controlled trials confined to people with hypertension or diabetes found no strong evidence that a cardiovascular risk assessment performed by a clinician improves health outcomes. Conclusion: The performance of the Framingham risk scores varies considerably between populations and evidence supporting the use of cardiovascular risk scores for primary prevention is scarce.